2000
DOI: 10.1002/(sici)1099-1085(20000430)14:6<1083::aid-hyp998>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Continuous daily hydrograph simulation using duration curves of a precipitation index

Abstract: The paper describes a parsimonious approach for generating continuous daily stream-¯ow time-series from observed daily rainfall data in a catchment. The key characteristic in the method is a duration curve. It is used to convert the daily rainfall information from source rain gauges into a continuous daily hydrograph at the destination river site. For each source rain gauge a time-series of rainfall related`current precipitation index' is generated and its duration curve is established. The current precipitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 14 publications
(17 reference statements)
0
21
0
Order By: Relevance
“…Plot of the daily hydro-chemographical dataset recorded at the main monitoring station (BS16_01) and the 10-min rainfall plot at the Sanza rain gauge. Legend: Numbers indicate the selected events; horizontal lines are representative of the reference parameters ranges; black dashed-double dot lines are for EC maxima in the dry period; black dashed-dotted line is for EC minimum during the dry period; black dashed line is for EC maximum in the wet period; black dotted line is for EC minimum in the wet period; grey dashed line indicates the Q minima in the wet period; grey dotted line indicates the average Q maximum in the wet period; finally, the grey dashed-dotted curve indicates the theoretical annual baseflow curve of the catchment during the period under consideration; yellow box delimitates the wet period events; grey box delimitates the transition period events; red box delimitates the dry period According to Smakhtin and Masse (2000), the corrected antecedent precipitation indexes (CPI) is calculated by adopting the following equation:…”
Section: Observed Datamentioning
confidence: 99%
“…Plot of the daily hydro-chemographical dataset recorded at the main monitoring station (BS16_01) and the 10-min rainfall plot at the Sanza rain gauge. Legend: Numbers indicate the selected events; horizontal lines are representative of the reference parameters ranges; black dashed-double dot lines are for EC maxima in the dry period; black dashed-dotted line is for EC minimum during the dry period; black dashed line is for EC maximum in the wet period; black dotted line is for EC minimum in the wet period; grey dashed line indicates the Q minima in the wet period; grey dotted line indicates the average Q maximum in the wet period; finally, the grey dashed-dotted curve indicates the theoretical annual baseflow curve of the catchment during the period under consideration; yellow box delimitates the wet period events; grey box delimitates the transition period events; red box delimitates the dry period According to Smakhtin and Masse (2000), the corrected antecedent precipitation indexes (CPI) is calculated by adopting the following equation:…”
Section: Observed Datamentioning
confidence: 99%
“…The correlation between maximum annual discharge and the precipitation in the preceding n days (including the day of maximum discharge as the last day in the series) was computed. Additionally, the current precipitation index (C PI ; Smakhtin and Masse, 2000), which corresponds to the better known antecedent precipitation index (A PI ) plus the precipitation on the current day, was computed iteratively as…”
Section: Beyond the Daily Perspectivementioning
confidence: 99%
“…Also reliable rainfall gauges which provide inputs for these models do not always exist at the locations of interest. Smakhtin and Masse [2000] suggested that these types of complex and information consuming methods may not always be appropriate in data-poor regions, where comparable results can be achieved by applying the pragmatic techniques of data generation.…”
Section: Introductionmentioning
confidence: 99%
“…Smakhtin et al [1997] and Smakhtin [1999] illustrated the steps required to use the spatial interpolation technique and flow duration curves to generate complete streamflow time series. Smakhtin and Masse [2000] extended the FDC based spatial interpolation method to generate daily streamflow information at ungauged sites from observed rainfall data. Mohamoud [2008] used a FDC based sequential generation scheme, instead of the spatial interpolation method of Hughes and Smakhtin [1996], to construct daily streamflow series.…”
Section: Introductionmentioning
confidence: 99%